Atrophy of the Posterior Cricoarytenoid Muscle as an Indicator of Recurrent Laryngeal Nerve Palsy - Vitale Romo, Laura (AJNR Am J Neuroradiol, 1999)
BACKGROUND AND PURPOSE: The posterior cricoarytenoid (PCA) muscle is one of the intrinsic muscles of the larynx innervated by the recurrent laryngeal nerve. As such, recurrent laryngeal nerve palsy should not only result in paralysis of the true vocal cord or thyroarytenoid muscle but also in a similar change in the PCA muscle. The ability of CT and MR imaging to depict denervation atrophy in the PCA muscle in patients with recurrent laryngeal nerve palsy was evaluated. METHODS: Two investigators reviewed the CT and/or MR studies of 20 patients with a clinical history of vocal cord paralysis. The appearance of the PCA muscle was given a rating of 0, 1, 2, 3, or 4, with 0 being definitely normal and 4 being definitely abnormal or atrophic. Each study was also reviewed for the presence or absence of other features of vocal cord paralysis: thyroarytenoid muscle atrophy, anteromedial deviation of the arytenoid cartilage, an enlarged piriform sinus and laryngeal ventricle, and a paramedian cord. RESULTS: Atrophy of the PCA muscle was shown unequivocally in 65% of the cases and was most likely present in an additional 20%. The frequency with which other features of vocal cord paralysis were seen was as follows: thyroarytenoid atrophy, 95%; anteromedial deviation of the arytenoid cartilage, 70%; enlarged piriform sinus, 100%; enlarged laryngeal ventricle, 90%; and a paramedian cord, 100%. CONCLUSION: Atrophy of the PCA muscle may be commonly documented on CT and MR studies in patients with recurrent laryngeal nerve palsy and vocal cord paralysis, and therefore should be part of the constellation of imaging features of vocal cord paralysis. This finding is particularly useful when other imaging findings of vocal cord paralysis are absent or equivocal.